2011
DOI: 10.1021/nn200126a
|View full text |Cite
|
Sign up to set email alerts
|

Ce3+ Ions Determine Redox-Dependent Anti-apoptotic Effect of Cerium Oxide Nanoparticles

Abstract: Antioxidant therapy is the novel frontier to prevent and treat an impressive series of severe human diseases, and the search for adequate antioxidant drugs is fervent. Cerium oxide nanoparticles (nanoceria) are redox-active owing to the coexistence of Ce(3+) and Ce(4+) oxidation states and to the fact that Ce(3+) defects, and the compensating oxygen vacancies, are more abundant at the surface. Nanoceria particles exert outstanding antioxidant effects in vivo acting as well-tolerated anti-age and anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
343
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 368 publications
(361 citation statements)
references
References 60 publications
13
343
2
3
Order By: Relevance
“…However, a proper dose has to be determined; otherwise, the delayed effects induced by low doses of ceria could be ineffective to adequately protect cells against an excess of ROS. Another noteworthy finding is the long-term antioxidant action of nanoceria, unprecedented in the conventional antioxidant drugs, 26 which is persistent up to 7 days and only due to the nanoparticles uptaken from the cells, as confirmed by the untreated controls. We speculate that this could be related to a possible autoregenerative reactive cycle of cerium very likely activated in vitro, 44 thus allowing a continuous regeneration of the antioxidant activity, which could favor its activity over time with a single nanoparticle administration.…”
Section: Articlementioning
confidence: 79%
See 1 more Smart Citation
“…However, a proper dose has to be determined; otherwise, the delayed effects induced by low doses of ceria could be ineffective to adequately protect cells against an excess of ROS. Another noteworthy finding is the long-term antioxidant action of nanoceria, unprecedented in the conventional antioxidant drugs, 26 which is persistent up to 7 days and only due to the nanoparticles uptaken from the cells, as confirmed by the untreated controls. We speculate that this could be related to a possible autoregenerative reactive cycle of cerium very likely activated in vitro, 44 thus allowing a continuous regeneration of the antioxidant activity, which could favor its activity over time with a single nanoparticle administration.…”
Section: Articlementioning
confidence: 79%
“…The present study was designed to verify to which extent ceria nanoparticles could contribute to control the oxidative stress and growth of adult cardiac progenitor cells. The CeO 2 nanoparticles used were the same described in previous works, 2,26 …”
Section: à3mentioning
confidence: 99%
“…2,[7][8][9] In a few cases, nanoceria protected cells from oxidative stress induced by ROS or radiation. [10][11][12][13][14] It was also reported that nanoceria protects normal cells but not cancer cells. 15 On the other hand, CeO2 nanorods with a high aspect ratio had pro-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…This parameter can be adjusted, for example, via the introduction of CeO 2 nanoparticles doped with other rare earth elements [51]. The use of gadolinium is quite promising indeed [52][53][54].…”
Section: The Hypothesis Assessment and Reviewmentioning
confidence: 99%